Sektor Ekonomi Kreatif Kuliner Solusi Bagi Perlambatan Pertumbuhan Ekonomi Daerah Kabupaten Fakfak - Ardha Puspita Sari; Els Tieneke Rieke Katmo; Agus I. Sumule; Diana N. Irbanyanti; Indra Irianti (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2020)
Creative economic is a sustainable development strategy in addressing slow economic growth that occurred in Indonesia as well as in Fakfak, a natural resources richest region. Economic structure alteration from agriculture as primary sector to industry and information sectors indicated the need of innovation and creativity as a new source of sustainable economic growth. Creative economic can be a solution to impove regional economic in Fakfak which have slow economic growth, and high number of unemployement. Result of Hirarchy Process Analysis (HPA) shows that culinary is a potential creative economic sector apart from craft and tourism. This is caused by highest scores that achieved from several supported elements in culinary sector such as human resources, natural resources, cost, market access, technology and infrastructure and institutions. The HPA result also indicated that local government through its economic policies has played important role in supporting kuliner sector as well as economic development program of BP Tangguh, bank and universities or academics. Therefore, increase production and product diversification of local resources based culinary is still needed.